Nitrogen addition promotes soil phosphorus availability in the subalpine forest of eastern Tibetan Plateau - Liu, Ye; Bing, Haijian; Wu, Yanhong; Zhu, He; Tian, Xin; Wang, Zhiguo; Chang, Ruiying (Journal of soils and sediments, 2022)
Purpose The biogeochemical cycling of phosphorus (P) is essential for maintaining plant productivity and thus plays a vital role in soil carbon sequestration. However, how soil P availability responds to increasing atmospheric nitrogen (N) deposition in subalpine forests remains unclear. The aims of this study are to explore the responses of P bioavailability in the subalpine soils of eastern Tibetan Plateau to different N addition levels. Materials and methods A field experiment with three N addition gradients (0, 8, and 40 kg N ha −1 year −1 ) was performed in the Abies fabri dominated forest of Gongga Mountain, eastern Tibetan Plateau. The soil P fractions in organic layer and mineral layers (0–5, 5–10, 10–20 cm) were analyzed to reveal their responses to different N addition levels, and the key drivers regulating soil P availability under the N addition were also deciphered. Results and discussion The low N addition did not alter the concentrations of total P and its fractions in the soils, while the high N addition significantly increased the concentrations of bioavailable P (AP). The results of structure equation models suggest that the decrease in microbial biomass and energy demand (dissolved organic carbon, DOC) of microorganisms under high N addition probably promotes the turnover and release of organic P rather than P immobilization. Soil P fractions displayed a significant difference among the soil depths, while the N addition did not alter their vertical distribution patterns. Soil moisture, pH, soil organic carbon, DOC, and microbial biomass controlled the vertical distribution of AP, while the oxides or minerals of aluminum determined the variation in other P fractions. Conclusions High N deposition rate can promote soil P availability in the subalpine forest, while N addition did not alter the vertical distribution patterns of soil P, suggesting a strong regulation of initial conditions on its response sensitivity to N deposition. Although short-term N deposition dose not strongly alter soil P transformation in the subalpine forest, the varied availability of soil P needs to be concerned under the increasing N deposition rate in the future.